Pengaruh Penerapan Metode Eksperimen terhadap Hasil Belajar Siswa - Nasyiatul Asiyah Nasya; Dwi Fitri Wahyuni; Usman Efendi; Mutiara Triadinda (Jurnal Penelitian Pendidikan, 2022)
The purpose of this study was to determine the extent of the influence of the experimental method on the learning outcomes of fourth grade students of MI Nurul HUDA Sukaraja in completing the tasks listed in the book theme 3 sub-theme 1. The approach applied in this study was a quantitative approach with an experimental method. This research was conducted at MI Nurul Huda, precisely in class IV with a population of 60 people and a sample of 30 people. Student learning outcomes in theme 3 sub-theme 1 Hewan dan Tumbuhan di Lingkungan Rumahku which apply the Experimental method at MI Nurul Huda Sukaraja totaling 30 students, the smallest student average score is 75 and the largest is 100. Student learning outcomes for class IV theme 3 sub-theme 1 which did not apply the Experimental method at MI Nurul Huda Sukaraja, totaling 30 students, the smallest student learning outcome score was 55 and the largest was 85 with an average score of 65.6. The results of testing the hypothesis that there is a significant influence between the experimental method on learning outcomes in theme 3 sub theme 1 MI Nurul Huda Sukaraja.